MENERAPKAN PRINSIP KERAJAAN ALLAH DALAM KEHIDUPAN SEHARI-HARI: PENDEKATAN KONSTRUKTIF UNTUK TRANSFORMASI SPIRITUAL DAN SOSIAL - Heintje B. Kobstan; Evelyn Tjitojo (Diegesis : Jurnal Teologi, 2024)
This study explores applying the principles of the Kingdom of God in the daily lives of Christians with a constructive approach that focuses on spiritual and social transformation. The Kingdom of God, often understood as an eschatological reality, is also present in today's world through values ​​such as love, justice, forgiveness, and peace. This study uses a qualitative and library research approach to analyze relevant theological and biblical sources. The study's results indicate that the principles of the Kingdom of God can be internalized through personal reflection, Christian ethics education, and involvement in a supportive community. This strategy aims to shape the character of Christians to be in line with the culture of the Kingdom of God so that they can be light and salt in society. With consistent application, it is hoped that people can experience spiritual transformation and positively impact the social environment.